THE PARTICIPATION OF UZBEK YOUTH AND SKILLED PROFESSIONALS IN THE GLOBAL LABOR MARKET (Global Economic Review: Journal of Economics, Policy, and Business Development, 2026)
This article explores the participation of Uzbek youth and skilled professionals in the global labor market, synthesizing insights from recent research by both local and international scholars. The study highlights the importance of labour migration as a means of exposure to worldwide work standards, professional development, and skill acquisition. Research like Rasulov (2025) and Masharipov (2025) shows how migration improves language skills, technical proficiency, and real-world experience, making young professionals more employable when they return to Uzbekistan. According to Suvpulatov (2025) and Sunnatov (2025), the study also looks at methods for incorporating young people into developing and sustainable job areas, such as the digital economy and green industries. According to Boltaev (2025), human capital development, ongoing skill development, and alignment with labour market demands are highlighted as critical elements influencing young participation in labour relations. Furthermore, Askarova's (2024) assessment of foreign best practices in youth employment policy offers important insights for implementing successful tactics in Uzbekistan. The structural features of the labour market, such as formal and informal employment patterns, gender distribution, and migration trends, are further demonstrated by statistical analyses conducted by Shayusupova and Khasanov (2019). Despite these realisations, the literature identifies a number of unexplored topics. These include social equality and gender challenges, regional differences between urban and rural areas, employer expectations and sector-specific skill gaps, the quality of domestic job options, and the effects of digital transformation and emerging technologies on the labour market. In order to create complete policies that improve young employment, promote professional development, and improve Uzbekistan's standing in the international labour market, it is imperative that these gaps be addressed. By emphasising the interaction between migration, skill development, and labour market dynamics, this research advances our knowledge of the variables influencing youth participation and mobility. It offers policy suggestions to enhance worker readiness, guarantee fair access to opportunities, and promote Uzbekistan's sustainable economic growth.